Peran Guru Pembimbing Khusus dalam Menangani Kesulitan Belajar bagi Anak Slow Learner di SDN Cimone 7 - Nurfadhillah, Septy; Afifah, Adilah; Putri, Shindy Rajna; Halimah, Siti (MASALIQ, 2022)
This research is motivated by the existence of education that is intended for all children, including children with special needs. Children with special needs have different characters, especially Slow Learners in learning are still experiencing difficulties. Therefore, special mentor teachers are needed to help them provide a better education according to their character. The formulation of the problem of this research is how the role of a special supervisor teacher for Slow Learners at SDN Cimone 7. The purpose of this study is to determine the role of a special supervising teacher for Slow Learners at SDN Cimone 7. This type of research is qualitative research. Data collection techniques used are observation, interviews, documentation and triangulation of sources. The results of this study indicate that the role of special supervising teachers includes: designing and implementing specific programs, identifying, assessing and compiling individual learning programs, modifying teaching materials, conducting evaluations, and making reports on programs and the development of children with special needs. With these roles, most children with special needs in public elementary schools can provide good services. Suggestions for this research are the supervising teachers always encourage students to study hard at home and at school, and provide learning facilities that support the educational development of their students